PENGARUH BRAND IMAGE, ONLINE CUSTOMER REVIEW DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE - Puspita, Anisa; Ichsannudin; Ratnanto, Sigit (Universitas Nusantara PGRI Kediri, 2022)
The shift in consumer behavior from direct purchases in stores to online purchases makes the Shopee marketplace very attractive to consumers. This research is useful for knowing the influence of brand image, online customer review and price on purchasing decisions. A quantitative approach with causality research techniques is used in this study. In this study, the population was Management students at Nusantara University, PGRI Kediri, who had made online purchases of products on the Shopee marketplace. With a total of 40 respondents nonprobability sampling technique was used for sampling in this study. The technique of collecting data in the field is in the form of a questionnaire. The research instrument was tested using validity and reliability tests. The f test and t test were used as hypothesis testing. Based on the results of the partial and simultaneous research, it shows that the brand image, online customer review and price variables have an effect on purchasing decisions in the Shopee marketplace.